PREVENTION OF FORWARD HEAD POSTURE ON STUDENTS DURING ONLINE LEARNING IN THE COVID-19 PANDEMIC - Tri Suciati (Conferences of Medical Sciences Dies Natalis, 2021)
To prevent the spread of highly contagious coronavirus, the government regulates the health protocol, such as limitation of gathering, close the school and changing the education system from conventional to virtual started level elementary to even college level. As one of the solutions to learn media learning, the use of smartphones is increasingly significant. The longer duration of using a smartphone will cause a condition named Forward Head Posture.Forward head posture is one of the most common types of postural abnormalities. It is caused by the repetitive position while using a smartphone. The mechanism can be explained by the motion of looking down such as when using a smartphone. As a result, it encourages repetitive use of the head and neck muscles. Anatomically, it can be explained that the upper cervical vertebrae are hyperextended and shifted forward. Exposure to constant loads on craniovertebral extension muscle and non-contractile structure cause changes in biomedical motion, with every one inch the increase in distance from the head and neck, it will increase the gravitation tenfold. Increase stress eventually caused musculoskeletal damage or pain.